Lornoxicam gastro retentive floating matrix tablets: Design and in vitro evaluation - S Sathiyaraj; Ramya D Devi; Vedha B.N Hari (Wolters Kluwer Medknow Publications, 2011)
The objective of this present investigation is to prolong the gastric residence time of Lornoxicam by fabricating it into a floating sustained release matrix tablets. Lornoxicam, a potent oxicam group of non-steroidal anti-inflammatory drugs, suffers from relatively short half life of 2 to 3 hrs showing maximal absorption in proximal gastro intestinal tract region necessitating its need to be formulated as a floating sustained release matrix tablets. In this current investigation, hydroxyl propyl methyl cellulose K15M, a high viscous grade polymer with apparent viscosity of 15,000 cps, was kept as a variable (10-50%) and calcium carbonate (13%) was used as a gas generator. The prepared blends were subjected for its pre-formulation characterization. The directly compressed tablets were evaluated for physical parameters such as weight uniformity, hardness, friability, drug content, in-vitro buoyancy with axial and radial enlargement measurement, swelling index. From the investigation it was observed that the buoyancy lasted for up to 24 hrs. Fourier transform infra-red spectroscopy peaks assured the compatibility of the drug with excipients and confirmed the presence of pure drug in the formulation. It was supported by in-vitro dissolution studies; and the dissolution data was subjected to various release kinetic models to understand the mechanism of drug release.